2017
DOI: 10.1186/s12909-017-0995-z
|View full text |Cite
|
Sign up to set email alerts
|

Goleman’s Leadership styles at different hierarchical levels in medical education

Abstract: Background: With current emphasis on leadership in medicine, this study explores Goleman's leadership styles of medical education leaders at different hierarchical levels and gain insight into factors that contribute to the appropriateness of practices. Methods: Forty two leaders (28 first-level with limited formal authority, eight middle-level with wider program responsibility and six senior-level with higher organizational authority) rank ordered their preferred Goleman's styles and provided comments. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Senior leadership, as outlined above, derives power from the position held in the organization, or through the medical hierarchy an assumption of an expert role. 6,7 By contrast, clinical leadership calls for health-care professionals to draw on their clinical experience and knowledge to provide leadership focused on patient care. Edmonstone 18 notes clinical leaders tend to (1) use persuasion, rather than hierarchical power; (2) prefer evidence-based and planned change in consultation with colleagues; and (3) use reflective practice rather than a technical-rational approach.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Senior leadership, as outlined above, derives power from the position held in the organization, or through the medical hierarchy an assumption of an expert role. 6,7 By contrast, clinical leadership calls for health-care professionals to draw on their clinical experience and knowledge to provide leadership focused on patient care. Edmonstone 18 notes clinical leaders tend to (1) use persuasion, rather than hierarchical power; (2) prefer evidence-based and planned change in consultation with colleagues; and (3) use reflective practice rather than a technical-rational approach.…”
Section: Leadershipmentioning
confidence: 99%
“…Despite being outdated, the traditional leadership model in medicine is hierarchical 6 with those in senior roles utilizing "top down" approaches of leadership arising from their positional power and perceived expertise. 7 Genomic medicine usurps this convention by providing opportunities for early career medical practitioners to lead different areas of clinical genomics delivery (e.g., in clinical genetics, nephrology, neurology, immunology). This raises interesting parallels with digital technologies: just as we talk about digital natives (i.e., those born in the digital era) and migrants (i.e., those who came to digital technologies later in their life) 8 clinical genomics too has natives and migrants.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative that the person considering the chief fellow role is passionate about the mission of the role. The chief fellow would benefit from some faculty development on different leadership styles (eg, visionary, coaching, affiliative, democratic, pacesetting, commanding), 6 how to approach conflict resolution, and other common leadership situations. A successful chief fellow should aim to adapt to different leadership styles based on the unique situation.…”
Section: What Constitutes An Effective Chief Fellow?mentioning
confidence: 99%
“…For example, Tiel and colleagues demonstrated that patient mortality is lower when trauma teams are trained in teamwork, including leadership skills [10]. One such key skill is coordination [11] or, as Marks et al put it, "orchestrating the sequence and the timing of interdependent actions" [12]. Teamwork in emergencies furthermore should be contextually adaptive and account for team member experience and patient acuity [13].…”
Section: Introductionmentioning
confidence: 99%